Effects of Al, Ti, and Cr content with different interlayer configurations on tribological behavior of AlCrN and AlTiN multilayer coatings - Yilmaz, Mustafa Alper; Dogus, Ozkan; Turkuz, Cenk; Erdem, Cihan; Kucukyildirim, Bedri Onur (SAGE PUBLICATIONS LTD, 2023)
In this study, AlCrN and AlTiN coatings with various interlayer numbers and compositions were deposited on AISI D2 cold work tool steels using cathodic arc-physical vapor deposition to enhance the adhesive and abrasive wear resistance of cold forming tools. Linear reciprocating tribometer experiments were conducted at 15 and 30 N loads under dry sliding conditions to evaluate the wear resistance and friction characteristics of these coatings. The coatings were chemically and morphologically characterized using an optical microscope, an atomic force microscope, a scanning electron microscope equipped with energy-dispersive X-ray spectroscopy, and X-ray diffraction analysis. Wear scars were examined with an optical profilometer after the tribometer tests to determine wear volumes and wear mechanisms. The results showed that AlTiN coating with six interlayers could be a cold work steel coating with nearly 6 times lower wear rate compared to AlCrN coatings at 3.1 GPa contact pressures.
Keywords: Arc-physical vapor deposition coatings; cold forming tool steel; abrasive wear; AlTiCrN interlayers; MECHANICAL-PROPERTIES; INTERFACIAL ADHESION; THERMAL-STABILITY; WEAR-RESISTANCE; STEEL; FRICTION; IMPROVEMENT; PARAMETERS; HARDNESS; Materials Science